LncRNA RP11-551L14.4 suppresses breast cancer development by inhibiting the expression of miR-4472 - Wang, Bin; Chen, Hang; Yang, Rui; Xing, Lei; Chen, Chuan; Chen, Junxia (PeerJ, 2022)
Background Previous studies have been reported that long non-coding RNA (lncRNA) can regulate the expression of genes which are involved in many important cellular processes The potential role of lncRNA RP11-551L14.4 in the development of breast cancer and the possible regulatory mechanisms was investigated. Methods Quantitative real-time polymerase chain reaction (qRT-PCR) was conducted to analyze RP11-551L14.4 expression in 36 paired breast cancer tissues and adjacent tissues. The expression of RP11-551L14.4 in multiple breast cancer cell lines was detected by qRT-PCR. Meanwhile, overexpression of RP11-551L14.4 models was established using lentivirus in BT474 and T47D breast cancer cells. Cell counting kit-8 (CCK-8), cell colony formation and cell cycle assays were performed to detect the effects of RP11-551L14.4 on the biological function of breast cancer cells. Besides, bioinformatics techniques, dual luciferase reporter gene assay and rescue experiments were used to investigate the potential mechanisms. Results RP11-551L14.4 expression was negatively associated with the advanced tumor stage. Breast cancer patients with low RP11-551L14.4 expression manifested a poorer prognosis. The results of qRT-PCR showed that RP11-551L14.4 expression in breast cancer tissues was significantly lower than in adjacent tissues. Meanwhile, overexpression of RP11-551L14.4 significantly decreased the cell proliferation and cell cycle. Bioinformatics technology showed that RP11-551L14.4 could complementarily bind to miR-4472. qRT-PCR results indicated that the expression levels of miR-4472 and RP11-551L14.4 in breast cancer were negatively correlated. Luciferase reporter gene assay showed that miR-4472 remarkably decreased the relative luciferase activity of the wild-type RP11-551L14.4 vector. miR-4472 is a direct target gene of RP11-551L14.4. miR-4472 levels were reduced, and repulsive guidance molecule A (RGMA) mRNA or protein levels were increased after overexpression of RP11-551L14.4 in the breast cancer cells. miR-4472 reversed the effects caused by RP11-551L14.4 in breast cancer cells. Conclusion RP11-551L14.4 expression was remarkably decreased in breast cancer tissues and cells. RP11-551L14.4 may inhibit the malignant progression of breast cancer by regulating miR-4472 expression.
Keywords: RP11-551L14.4; miR-4472; Breast cancer; Proliferation